PENGARUH MODAL USAHA, LAMA USAHA, DAN LOKASI USAHA TERHADAP PENDAPATAN PEDAGANG PASAR SUNGGINGAN BOYOLALI: (STUDI KASUS PEDANGGANG PASAR SUNGGINGAN) - Ovi Arizka Maeshinta; Indra Lila Kusuma; Wikan Budi Utami (CV. Denasya Smart Publisher, 2024)
The purpose of this research is to analyze the impact of business capital, business location, and business location on the income of Boyolali market traders. The population at this start is a merchant in the Sunggingan Market of Boyolali district. The sample of this study consisted of 100 respondents, taken with the Slovin formula. The variables used include enterprise capital (X1), enterprise duration (X2), enterprise location (X3), and income (Y). The data analysis used in this study uses descriptive analysis, validity tests, reliability tests, and classical assumption tests, with hypothesis testing using double linear regression analysis, the F test, the t test, and the determination coefficient. The results show that partially the variable that affects the trader's income is the location of the business (X3), with a t test result of 2,779 > t table of 1,98498. Whereas the business capital (X1) and the duration of the enterprise (X2) have no significant influence on the traders' income, with the result of the capital test count of the company (X1) |-1,176 | < t table 1.98498, as well as the results of the long-term enterprise test of 1,160 < t table 1.98498.